2020
DOI: 10.3389/fpls.2020.600021
|View full text |Cite
|
Sign up to set email alerts
|

RSD1 Is Essential for Stomatal Patterning and Files in Rice

Abstract: Stomatal density is an important factor that determines the efficiency of plant gas exchange and water transpiration. Through forward genetics, we screened a mutant rice stomata developmental defect 1 (rsd1-1) with decreased stomatal density and clustered stomata in rice (Oryza sativa). After the first asymmetric division, some of the larger sister cells undergo an extra asymmetric division to produce a small cell neighboring guard mother cell. Some of these small cells develop into stomata, which leads to sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…EPFL10 mutation reduces stomatal density but does not significantly alter stomatal conductance and carbon assimilation, which leads to higher water preservation than that in wild-type rice and improved drought resilience [134]. RSD1 mutation results in stomatal cluster distribution, decreased stomatal density, significant down-regulation of stomatal development-related gene OsSDD1, and enhanced drought tolerance of the mutant [135].…”
Section: Regulating Stomatal Density and Stomatal Opening And Closingmentioning
confidence: 99%
“…EPFL10 mutation reduces stomatal density but does not significantly alter stomatal conductance and carbon assimilation, which leads to higher water preservation than that in wild-type rice and improved drought resilience [134]. RSD1 mutation results in stomatal cluster distribution, decreased stomatal density, significant down-regulation of stomatal development-related gene OsSDD1, and enhanced drought tolerance of the mutant [135].…”
Section: Regulating Stomatal Density and Stomatal Opening And Closingmentioning
confidence: 99%
“…For instance, the CRISPR-Cas9 based stomata developmental defect 1 ( osrsd1 ) mutants had decreased stomatal density that prevented water loss under dehydration stress. Consequently, mutant lines also exhibited altered expression of other stomatal related genes i.e., stomatal density and distribution 1 ( OsSDD1 ), and showed tolerance against drought stress (Yu et al 2020 ). Lu et al ( 2020 ) identified two drought-sensitive genes ( OsAAA-1 and OsAAA-2 ) through screening of the activation tagging population.…”
Section: Can Crispr Help To Breed New Climate-resilient Transgene-fre...mentioning
confidence: 99%